Physicians' Opinions on Anticoagulant Therapy in Patients with a Limited Life Expectancy - Huisman, Bregje A.A.; Geijteman, Eric C.T.; Kolf, Nathalie; Dees, Marianne K.; van Zuylen, Lia; Szadek, Karolina M.; Steegers, Monique A.H.; van der Heide, Agnes (Seminars in Thrombosis and Hemostasis, 2021)
Patients with a limited life expectancy have an increased risk of thromboembolic and bleeding complications. Anticoagulants are often continued until death, independent of their original indication. We aimed to identify the opinions of physicians about the use of anticoagulants at the end of life. A mixed-method research design was used. A secondary analysis was performed on data from a vignette study and an interview study. Participants included general practitioners and clinical specialists. Physicians varied in their opinions: some would continue and others would stop anticoagulants at the end of life because of the risk of thromboembolic or bleeding complications. The improvement or preservation of patients' quality of life was a reason for both stopping and continuing anticoagulants. Other factors considered in the decision-making were the types of anticoagulant, the indication for which the anticoagulant was prescribed, underlying diseases, and the condition and life expectancy of the patient. Factors that made decision-making difficult were the lack of evidence on either strategy, uncertainty about patients' life expectancy, and the fear of harming patients. Which decision was eventually made seems largely dependent on the choice of the patient. In conclusion, there is a substantial variation in physicians' opinions regarding the use of anticoagulants in patients with a limited life expectancy. Physicians agree that the primary goal of medical care at end of life is the improvement or preservation of patients' quality of life. An important barrier to decision-making is the lack of evidence about the risks and benefits of stopping anticoagulants.
Keywords: anticoagulants; bleeding; mixed methods; palliative care; venous thromboembolism